Empowering alkali lignin with high performance in pickering emulsion by selective phenolation for the protection and controlled-release of agrochemical. (10th March 2022) - Yu, Xiaona; Chen, Shanshuai; Wang, Weichen; Deng, Tiansheng; Wang, Hongliang
Abstract: Lignin is a versatile bioaromatic polymer, with great potentials in the preparation of advanced materials due to its anti-UV and anti-oxidant properties. However, the high heterogeneity of lignin seriously hinders its practical applications. In this study, alkali lignin with limited content of hydroxyl groups and a wide distribution of molecular weight was modified by selective phenolation, which not only resulted in a dramatical increase in the content of phenolic hydroxyl groups but also led to a more uniform structure of lignin. Catechol, as compared with phenol and pyrogallol, was the most suitable phenolation reagent to reacted with lignin, and the phenolic hydroxyl content of the catechol modified lignin increased by 318.89%. Besides, the molecular weight and polydispersity index of lignin after the modification decreased, which led to a small and regular size of lignin particles prepared by acid precipitation. Subseqently, lignin particles were used to prepare Pickering emulsions for avermectin (AVM) encapsulation, and the stability as well as the anti-UV and anti-oxidant capacities of Pickering emulsions prepared by using phenolated lignins as solid surfactants were obviously enhanced. The encapsulation efficiency of AVM in Pickering emulsions was also improved, which could reach high above 90%. Moreover, AVM protected by lignin-based Pickering emulsion could be controllably released in line with actual application demands, and the relatively high viscosity of emulsion could effectively avoid the loss of pesticide during spraying to the target. Graphical abstract: Image 1